Membranes as multi-agent systems: an application to dialogue modelling - Jiménez López, Dolores (2006)
Human-computer interfaces require models of dialogue structure that capture the variability and unpredictability within dialogue. In this paper, taking as starting point P systems, and by extending it to the concept of dialogue P systems through linguistic P systems we introduce a multi-agent formal architecture for dialogue modelling. In our model, cellular membranes become contextual agents by the adjunction of cognitive domains. With this method, the passage from the real dialogue to the P systems model can be achieved in a quite intuitive and simple way.